Problematika dan Strategi Pembelajaran pada Masa Pandemi di Wilayah Pesisir Kepulauan Buton - Firman Alamsyah Mansyur; Fahmil Ikhsan Taharu (Sang Pencerah: Jurnal Ilmiah Universitas Muhammadiyah Buton, 2021)
This study aims to explain the problems and strategies of schools and teachers in coastal areas of the Buton islands in carrying out learning during the Covid-19 pandemic. This research method is descriptive qualitative. Primary data are collected through online questionnaires, observations, and interviews. Research informants come from the elements of teachers, high school principals, students and parents of participants, especially Muhammadiyah High School. Secondary data is obtained through literature studies. The data are analyzed using qualitative data analysis method consisting of data reduction, data presentation, data interpretation and conclusion drawing. From the results of the study, it is concluded that there are various problems in the implementation of learning in high schools during the pandemic-Covid-19. The problems are strongly related to the unpreparedness of schools, teachers, parents, and students in facing the transformation of learning during the pandemic. In addition, network unpreparedness also greatly affects the transformation of learning from offline to online to ineffective. Therefore, there are various strategies that schools and teachers try to implement to carry out learning, both online and face-to-face through limited class meetings and home visits. The results of this study show that the implementation of learning during the pandemic does not run effectively due to very complex problems. The role of the government is very important in preparing facilities and infrastructure to support the implementation of learning during the pandemic covid-19.